Characterization of industrial onion wastes (Allium cepa L.): dietary fibre and bioactive compounds. - Benítez, Vanesa; Mollá, Esperanza; Martín-Cabrejas, María A.; Aguilera, Yolanda; López-Andréu, Francisco J.; Cools, Katherine; Terry, Leon A.; Esteban, Rosa M. (Cranfield University, 2011)
The food industry produces a large amount of onion wastes, making it necessary to search for possible ways for their utilization. One way could be to use these onion wastes as a natural source of high-value functional ingredients, since onion are rich in several groups of compounds, which have perceived benefits to human health. The objective of this work is to gain knowledge of any differences between the different onion wastes obtained from industry and non-commercial bulbs to use them as food ingredients rich in specific compounds. The results showed that brown skin and top-bottom could be potentially used as functional ingredient rich in dietary fibre, mainly in insoluble fraction, and in total phenolics and flavonoids, with high antioxidant activity. Moreover, brown skin showed a high concentration of quercetin aglycone and calcium, and top-bottom showed high concentration of minerals. Outer scales could be used as source of flavonols, with good antioxidant activity and content of dietary fibre. However, inner scales could be an interesting source of fructans and alk(en)yl cystein sulphoxides. In addition, discarded onions (cvs Recas and Figueres) could be used as a good source of dietary fibre, and cv Recas also as a source of phenolics compounds.